2006
DOI: 10.1080/10408440500534354
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Chemical Safety Assessment: A Multisector Approach to the Modernization of Human Safety Requirements

Abstract: Better understanding of toxicological mechanisms, enhanced testing capabilities, and demands for more sophisticated data for safety and health risk assessment have generated international interest in improving the current testing paradigm for agricultural chemicals. To address this need, the ILSI Health and Environmental Sciences Institute convened a large and diverse group of international experts to develop a credible and viable testing approach that includes scientifically appropriate studies that are neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 10 publications
0
33
0
3
Order By: Relevance
“…Non-linear TK, in which metabolism or excretion pathways available at lower blood concentrations are partly or fully saturated with increasing dose, may be a clear confounder both in appropriately designing toxicological studies and evaluating results for hazard and human risk assessment. Use of TK to inform human-relevant dose selection in animal toxicity studies has been affirmed in recent reviews and Organization for Economic Cooperation and Development (OECD) guidance on conduct of the EOGRT study Carmichael et al 2006;Cooper et al 2006;OECD 443, 2012a). The guidance recommended that top dose level(s) should not exceed the inflection point of onset of TK non-linearity if the inflection point dose was well separated from human exposures, and further concluded that toxicity limited to doses above the onset of non-linear TK behavior was not quantitatively relevant to human risk.…”
Section: Differentiating Potential Endocrine Modes Of Action Based Onmentioning
confidence: 99%
“…Non-linear TK, in which metabolism or excretion pathways available at lower blood concentrations are partly or fully saturated with increasing dose, may be a clear confounder both in appropriately designing toxicological studies and evaluating results for hazard and human risk assessment. Use of TK to inform human-relevant dose selection in animal toxicity studies has been affirmed in recent reviews and Organization for Economic Cooperation and Development (OECD) guidance on conduct of the EOGRT study Carmichael et al 2006;Cooper et al 2006;OECD 443, 2012a). The guidance recommended that top dose level(s) should not exceed the inflection point of onset of TK non-linearity if the inflection point dose was well separated from human exposures, and further concluded that toxicity limited to doses above the onset of non-linear TK behavior was not quantitatively relevant to human risk.…”
Section: Differentiating Potential Endocrine Modes Of Action Based Onmentioning
confidence: 99%
“…The findings in young adults are then taken into account during the assessment of the compound during different life stages, including reproduction, development, adolescence, and the elderly. The process for assessing the effects of agricultural chemicals on these life stages is the subject of the companion paper by the ACSA Life Stages Task Force (Cooper et al, 2006). A complete assessment can be made only by taking into account all of the data generated in the overall assessment.…”
Section: Definition Of the Scope Of Systemic Toxicitymentioning
confidence: 99%
“…Data are also generated to explore the effect of the chemical on reproduction and development. These studies have been considered by the ACSA Life Stages Task Force (Cooper et al, 2006). The data from these studies are used to identify and characterize the hazards of the substance, that is, what effects it causes and at which dose levels.…”
Section: Matching Current Studies With Exposure Durations For Risk Asmentioning
confidence: 99%
See 2 more Smart Citations